Promoting gifted students' creativity through design-based STEM activities - Costu, Fatma (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
BackgroundDesign-based STEM activities offer a unique opportunity to integrate creative problem-solving and critical thinking into education for gifted students, aligning with their intellectual and creative strengths. By emphasizing hands-on, non-IT-based tasks, this approach fosters both verbal and figural creativity, allowing students to explore interdisciplinary problems and develop innovative solutions without the immediate need for advanced technological skills.PurposeThis study aimed to investigate the effects of design-based STEM activities on the development of verbal and figural creativity in gifted students.SampleThe study involved 60 seventh-grade gifted students who were randomly divided into two groups: an experimental group (EG) (n = 30) and a control group (CG) (n = 30).Design and methodsThis study utilized a quasi-experimental pre-test - post-test control group design to examine the effects of design-based STEM activities on gifted students' creativity. While the EG participated in design-based STEM activities, the CG engaged in non-STEM teaching activities. Both groups received a total of 18 hours of instruction. Data was collected using the Torrance Test of Creative Thinking (TTCT) scale, and statistical analyses were conducted.ResultsThe findings showed significant improvements in favor of the EG for both verbal and figural creativity, indicating that design-based STEM activities can effectively enhance the creative skills of gifted students.ConclusionDesign-based STEM activities effectively enhance both verbal and figural creativity in gifted students by fostering critical thinking, problem-solving, and interdisciplinary learning. This approach provides an engaging, hands-on environment that nurtures creativity and equips students with essential skills for addressing complex, real-world challenges.
Keywords: STEM education; Design-based STEM; Giftedness; verbal creativity; figural creativity; TORRANCE TESTS; THINKING; Education & Educational Research